Cybersecurity Implications of 5G Networks: Threats, Potential Vulnerabilities, and Their Implications for National Security and Privacy - Asante, George; Balisane, Hewa; Salih, Abdulrahman; Aina, Folayo; Kure, Halima; Egho-Promise, Ehigiator (IAES Indonesian Section, 2025)
The rapid expansion of Fifth Generation (5G) networks represents a revolutionary shift in telecommunications technology, offering increased speed, higher connection density, and enhanced network efficiency. Nevertheless, these benefits have also attracted various security risks that threaten the protection of national security and the privacy of private citizens. This research investigates the cybersecurity challenges associated with 5G networks by analysing emerging threats, assessing vulnerabilities in 5G infrastructure, and evaluating their impact on national security and individual privacy. The research approach includes a literature review of various sources of knowledge and regulations or policies, as well as a quantitative analysis of network vulnerabilities through penetration testing and threat modelling. The study's results indicate that network slicing introduces new risks to a network, as it provides potential attackers with easy access to weaknesses that exist within isolated network slices. Furthermore, the incorporation of Internet of Things (IoT) devices increases the overall risk, as they often lack proper security measures. Lastly, the multi-tenant characteristic of 5G networks poses a challenge in creating secure isolation between various operators and service providers. This makes it imperative for organisations and service providers to enhance their security measures, such as encryption and access control policies, as well as overall policies, to help rectify these issues. These findings concluded significant implications across national security and privacy fronts. The study re-emphasizes the importance of a multi-sectoral approach to cybersecurity by industries, policy-makers, and academic scholars. Measures and techniques that are relevant to implementing specific safety tactics and regulations were proposed. The results of this study serve as a reference for 5G cybersecurity. The results offer recommendations that are useful in developing security measures to counter threats and improve the security posture of future 5G networks.